PENGEMBANGAN KOMPETENSI MANAJERIAL PNS MELALUI PELATIHAN KEPEMIMPINAN DI LEMBAGA ADMINISTRASI NEGARA - Delia Putri Rahmawati (Jurnal Administrasi Publik, 2023)
Civil servants need the competence to complete their work in carrying out their duties and functions. Every civil servant can develop technical, managerial, and socio-cultural competencies. This research focuses on developing managerial competencies, especially civil servants with structural positions. Managerial competency development is carried out through leadership training. National Institute of Public Administration (NIPA) is a supervisory agency with the authority to conduct leadership training nationally. This study concluded that eight managerial competencies are developed through leadership training: integrity, cooperation, results-oriented communication, public service, self and others development, managing change, and decision-making. Then there are driving factors in implementing leadership training, namely self-motivation, leader commitment, and inhibiting factors in leadership training due to budget and technology limitations.